Epidemiology of Acute Pancreatitis in the North Adriatic Region of Croatia during the Last Ten Years. (14th February 2013) - Stimac, Davor; Mikolasevic, Ivana; Krznaric-Zrnic, Irena; Radic, Mladen; Milic, Sandra
Abstract : Introduction . Several European studies have reported an increase in the incidence rate of acute pancreatitis (AP). Therefore, we studied the incidence rate of AP in the North Adriatic Region in Croatia, as well as epidemiological analysis concerning etiology, age, gender, and severity of disease. Methods . We analyzed 922 patients with confirmed diagnosis of AP (history, clinical and laboratory findings, and imaging methods) admitted to our hospital during a ten-year period (2000–2009). Epidemiological analysis was carried out focusing on incidence, demographic data, and etiology, as well as severity of the disease based on the Ranson and APACHE II scores. Results . The incidence rate varied from 24 to 35/100 000 inhabitants annually. Mean age was 60 ± 16 years. There were 53% men and 47% women among the patients. Most frequent etiologies of AP were biliary stones in 60% and alcohol abuse in 19% of patients. According to the Ranson and APACHE II scores, pancreatitis was considered to be severe in 50% and 43% of the cases, respectively. Conclusion . In our region the incidence of AP was around 30 per 100, 000 population per year during the ten-year period studied. The mean age at admission was 60 years and etiology was predominantly biliary. In our region, we have shown epidemiological characteristics of AP typical for Mediterranean countries.